Houses in motion the experience of place and the problem of belief in urban Malaysia - Baxstrom, Richard (Cultural memory in the present, 2008)
Tells about the transformation of urban space and the reordering of the demographic character of Brickfields, one of the oldest neighborhoods in Kuala Lumpur. This book combines methods of anthropological research and an engagement with the work of theorists such as Gilles Deleuze and Henri Lefebvre.